Ecological and economic improving of agricultural land use on regional level - Butenko, E.; Kasanchyk, V. (Land Management, Cadastre and Land Monitoring, 2017)
Land Reform in Ukraine is already a considerable period of time. Priority land reform was to be the formation of land market relations that would ensure continued efficient reallocation of land resources based on market self-regulation. Implementation of large-scale land reforms in these areas has caused huge problems of acute social, economic and environmental. Properly not the rational use and protection of land resources, reproduction of the productive potential of agricultural lands. Particularly acute problem of management and expanded reproduction of land resources as a basis for sustainable development of Ukraine. Pressing problem today is to resolve these matters in accordance with the principles of sustainable development. Particulary attention should be focused on the implementation of integrated land use by solving problems of the rational use of land, an important aspect of which is to optimize land use. Irrational land use system has led to serious environmental consequences, namely the presence of such manifestations of land degradation as erosion, technogenic pollution, secondary alkalinity, flooding and landslides. The high level of tilled land, including hills, a significant expansion of crops cultivated crops and almost complete cessation of work package for soil protection, violation of the cultivation leads to land degradation. The current state of land use Cherkasy region does not meet the requirements of environmental management. Violated environmentally acceptable ratio of arable land, natural grasslands, which adversely affects the stability of agricultural landscapes. Optimizing the efficiency of land use requires evidence-based approach to land. So based on upgraded inventory system and effective land management by taking into account environmental and economic component of their assessment, you can achieve a significant positive impact on the economy of the region and the state as a whole. The current system of land use must meet the following parameters: include complex of soil-reclamation measures to expanded reproduction of soil fertility, built on the optimal structure of agricultural land formations, consider advanced technologies and harmoniously coordinated in agricultural ecosystems. World experience shows that the efficiency of agriculture is possible only in conditions of heavy use soil by reducing investments in unproductive land. Land resources are one of the most important types of resource area. In modern conditions for intensive agricultural cultivation should involve productive agricultural land, one third should remain in it’s natural state that provide ecological balance in nature and will help produce more gross yield per unit area. The implementation of the proposed measures to optimize the structure of agricultural land Cherkasy region, namely the withdrawal areas and unproductive soils from intensive cultivation and further their conservation, will effectively use land without significant adverse effects on soils and simultaneously achieve a given economic effect. So, to start rationalizing land use should decrease the rate of tilled area to the optimum value (40%). Optimizing the efficiency of land use requires evidence-based approach to land. So based on upgraded inventory system and effective land management by taking into account environmental and economic component of their assessment, you can achieve a significant positive impact on the economy of the region and the state as a whole. Keywords: land resources, ecological and economic optimization, sustainable development, sustainable land use.